(untitled) (Andamios, Revista de Investigación Social, 2009)
This text states that citizen’s participation constitutes a societystate kind of relation which, before making reference to a bunch of institutional structures or to the logics of social organization, can be conceived as an interaction space, as well as for communication and differentiation between the state system and the social system. The text also sets out that the relation between the state and the society is a characteristic relation in contemporary societies; it is delimited (in its senses and orientations) by the regulation notions derived from the meaning of democracy and the concept of citizenship itself. The relation performs the function of regulating permanently the conflict assumed in the definition of public affairs and the political and social agendas.